Efficacy of Bortezomib plus dexamethasone as a first line treatment in newly diagnosed cases of Multiple Myeloma: A Single Centre Study in a Tertiary Care Hospital - Sharmin, Mahbuba; Islam, Mohammad Manirul; Aziz, Abdul; Shah, Salauddin; Rahman, Md Jalilur; Kabir, ASM Anwarul; Kabir, Amin Lutful; Hasan, Md Rashedul; Rahman, Farzana; Kabir, SM Humayun; et al. (Journal of Dhaka Medical College, 2020)
Background: Multiple Myeloma (MM) accounts for 1% of malignant tumors and 10%–15% of hematopoietic neoplasms. Bortezomib, a first in class proteasome inhibitor, induces apoptosis and growth arrest and reverse chemoresistence in Myeloma cell and has demonstrated no irreversible adverse effect on haemopoietic stem cell. Dexamethasone increases the response rate. Thus, Bortezomib plus dexamethasone represent highly effective regimen for previously untreated Multiple Myeloma cases and significantly higher response rates approximately 70%– 90% have been observed.This combination thus may serve the basis of future strands of care in Multiple Myeloma patients. Objective: The aim of the study was to assess the efficacy , safety and tolerability of Bortezomib in newly diagnosed cases of Multiple Myeloma patients in Bangladesh. Materials & Methods: This prospective observational study was carried out in the Haematology department of BSMMU from June 2017 to December 2018. Patients received inj. Bortezomib (1.3mg/m2 ) 4 cycles as an intravenous bolus on days 1,4,8,11 in a three week cycle (twice weekly administration) in indoor and same patients as day care basis in outpatients department. Dexamethasone at 40 mg was given intravenously or orally on the day of and day after inj Bortezomib.A self administered questionnaire containing different set of questions regarding Multiple Myeloma were used for data collection. Results: Among the study population, 93% of patients had anaemia followed by bone pain (86%) and renal impairment (39%). Out of 25 patients,complete response achieved in 13 patients (52%), where 4 patients(16%) showed partial response,6 (24%) showed very good partial response and 2 (8%) patients showed no response. The overall response rate was 92% belonged to partial,very goofd partial and no respone respectively. Death occurred in 3 cases (12%). 5 patients (20%) developed Bortezomib induced peripheral neuropathy.Life threatening intracranial haemorrhage occurred in two patients (8%). Death occurred in 3 cases (12%),2 patients due to intracranial haemorrhage and another from cardiac arrest. In this study,S. creatinine, â2 microglobulin and bony lesion variables showed significant association with treatment response. Conclusion: Bortezomib plus dexamethasone is a highly effective and safe regimen for previously untreated multiple myeloma patients. This novel therapy in myeloma represent a new trearment paradigm targeting both tumor and microenvironment which has markedly improve overall response(OR), long progression free survival (PFS) and overall survival (OS)across in all risk groups. Moreover,it can be administered safely in the outpatient setting provided by clinicians. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 34-41